2017
DOI: 10.1164/rccm.201608-1576oc
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Pediatric Pulmonary Arterial Hypertension Measured by Accelerometry. A Candidate Clinical Endpoint

Abstract: PA is markedly decreased in children with PAH. Accelerometer output correlated with clinical disease severity markers and may predict outcome. We showed an exciting potential of PA as a meaningful endpoint for clinical trials in pediatric PAH, although its clinical utility and prognostic value need to be further validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 44 publications
(50 reference statements)
1
35
0
Order By: Relevance
“…For example, the primary efficacy endpoint commonly measured in interventional pulmonary arterial hypertension trials in adults is the 6‐minute walk test (6MWT), which is a measure of exercise capacity . However, the 6MWT would not be a feasible endpoint to measure in infants and young children because they are not developmentally or physically capable of performing the test . In other instances, the relatively small pediatric patient population available or the infrequency of endpoint events often make it unfeasible to incorporate the adult endpoint into a pediatric trial because of the sample size that would be required to achieve adequate statistical power to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the primary efficacy endpoint commonly measured in interventional pulmonary arterial hypertension trials in adults is the 6‐minute walk test (6MWT), which is a measure of exercise capacity . However, the 6MWT would not be a feasible endpoint to measure in infants and young children because they are not developmentally or physically capable of performing the test . In other instances, the relatively small pediatric patient population available or the infrequency of endpoint events often make it unfeasible to incorporate the adult endpoint into a pediatric trial because of the sample size that would be required to achieve adequate statistical power to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring daily physical activity has also been suggested as an alternative tool to assess functional capacity in children. A recent pilot study using three-axis accelerometry in 29 children with PAH and 60 controls showed that physical activity was markedly decreased in children with PAH, and that accelerometer output correlated with clinical disease severity markers and predicted outcome [77]. Larger studies are in progress to validate the use of accelerometry output as a clinically meaningful end-point for clinical trials in paediatric PAH.…”
Section: Updates In Paediatric Ph Epidemiology and Classificationmentioning
confidence: 99%
“…Decreased physical activity, as measured by an actigraphy device worn on the wrist of adult PAH patients in the outpatient setting, has been shown to correlate with increased disease severity and worse prognosis [ 98 ]. A more recent study validated this finding in children with PAH, showing a positive correlation between actigraphy-measured physical activity, 6MWD, and improved functional class [ 99 ].…”
Section: Emerging Evaluation Techniquesmentioning
confidence: 69%